Effect of urban household farming on food security status in ibadan metropolis, oyo state, nigeria (2015)
Agriculture is an important tool for reducing the effects of household food insecurity, unemployment and poverty which are major problems in urban areas in Nigeria. Food insecurity continues to worsen in some urban areas of the country and many households resulted into urban farming as a means of coping. The study investigated the effect of urban household farming on food security status in Ibadan metropolis, Oyo State, Nigeria. Primary data was collected for the study using structured questionnaire. Two-stage sampling technique was employed for this study. The first stage involved the random selection of two urban local government areas from Ibadan metropolis. This was followed with the selection of 110 urban farming households from these local government areas. Data were analyzed using descriptive statistics, Foster-Greer-Thorbecke and probit regression. Results showed that sex, years of schooling, marital status, household size, access to extension agent, hired labor and type of farming enterprises are determinants of food security. The study recommends the policies that make extension services accessible to urban farmers and also skills development among others